Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1587/transinf.2018mup0007
|View full text |Cite
|
Sign up to set email alerts
|

Robust Image Identification with DC Coefficients for Double-Compressed JPEG Images

Abstract: In the case that images are shared via social networking services (SNS) and cloud photo storage services (CPSS), it is known that the JPEG images uploaded to the services are mostly re-compressed by the providers. Because of such a situation, a new image identification scheme for double-compressed JPEG images is proposed in this paper. The aim is to detect a single-compressed image that has the same original image as the double-compressed ones. In the proposed scheme, a feature extracted from only DC coefficie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 17 publications
(39 reference statements)
0
8
0
Order By: Relevance
“…A DC coefficient DC in each block is obtained by using the following equation, where I(x, y) represents a pixel value at the position (x, y) in a block. been reported that the features extracted from DC coefficients are effective for recompression in the conventional schemes [21], [22]. Therefore, the DC coefficients are used for the identification in this paper.…”
Section: Image Identification For Jpeg Imagesmentioning
confidence: 99%
See 1 more Smart Citation
“…A DC coefficient DC in each block is obtained by using the following equation, where I(x, y) represents a pixel value at the position (x, y) in a block. been reported that the features extracted from DC coefficients are effective for recompression in the conventional schemes [21], [22]. Therefore, the DC coefficients are used for the identification in this paper.…”
Section: Image Identification For Jpeg Imagesmentioning
confidence: 99%
“…Regarding requirement 3, image retrieval and the identification of encrypted images have never been considered for EtC systems, although image identification and retrieval schemes that are robust against JPEG compression have been proposed for unencrypted images [21]- [25]. However, the performance of these schemes is degraded in the case of identification between encrypted images and corresponding re-encrypted images, so, to satisfy all requirements, novel image identification methods are required.…”
Section: Introductionmentioning
confidence: 99%
“…Can detect lines, curves, patterns in the image. Mainly used in text recognition, number recognition, speech recognition [22][23].…”
Section: Image Recognition Algorithmmentioning
confidence: 99%
“…The range of the DC coefficients is [-1024,1016]. It has been reported that the features extracted from DC coefficients are effective for recompression in the conventional schemes [18,19]. Therefore, the DC coefficients are used for the identification in this paper.…”
Section: Image Identification For Jpeg Imagesmentioning
confidence: 99%
“…Regarding requirement 3, image retrieval and the identification of encrypted images have never been considered for EtC systems, although image identification and retrieval schemes that are robust against JPEG compression have been proposed for unencrypted images [18][19][20][21][22]. However, the performance of these schemes is degraded in the case of identification between encrypted images and corresponding re-encrypted images, so, to satisfy all requirements, novel image identification methods are required.…”
Section: Introductionmentioning
confidence: 99%